2007
DOI: 10.1159/000111533
|View full text |Cite
|
Sign up to set email alerts
|

RCAS1 Decidual Immunoreactivity during Cesarean Section in Scar Deciduosis: Immune Cell Presence and Activity

Abstract: Introduction:Scar deciduosis provides a research model that enables us to assess the impact of decidua on the activity and quality of the immune cells infiltrating this scar tissue. This unique model allows us to examine these processes under conditions excluding the impact of placental cells which, along with decidual cells, control the activity of immune cells under physiological conditions. RCAS1 is a protein responsible for the suppression of the cytotoxic immune response during gestation. The present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 86 publications
(36 reference statements)
1
13
0
Order By: Relevance
“…20,22,45 In the current study, we have observed the presence of B7-H4 macrophages at the maternal-fetal interface. However, the factor responsible for the restriction of the maternal immune system activity that increases with the initiation of labor is not clear.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…20,22,45 In the current study, we have observed the presence of B7-H4 macrophages at the maternal-fetal interface. However, the factor responsible for the restriction of the maternal immune system activity that increases with the initiation of labor is not clear.…”
Section: Discussionsupporting
confidence: 59%
“…In our previous study, one of the mechanisms observed to restrict the maternal immune system activity was the increase in the inhibitory activity of the decidua that is related to membrane proteins expressed by decidual cells and secreted to the fetoplacental microenvironment. 20,22,45 In the current study, we have observed the presence of B7-H4 macrophages at the maternal-fetal interface. To our knowledge, this is the first investigation to focus on the presence of B7-H4 suppressive macrophages in the decidua relative to the progression of labor.…”
Section: Discussionmentioning
confidence: 99%
“…RCAS1 is therefore responsible for the tumor escape from host immunologic surveillance and the creation of immune tolerance for tumor cells 31–42 . RCAS1 expression has been found in various malignant neoplasms and is related to the grade of the tumor, the stage of the disease, and the presence of lymph node metastases, as well as to a poorer prognosis 38 .…”
Section: Rcas1 In Tumor Microenvironment Remodelingmentioning
confidence: 99%
“…The infiltration of immune cells into the endometrium begins before ovulation and is limited to the early secretory cycle phase, 5 when the ovum passes through the Fallopian tube whether or not fertilization occurs. Cytotoxic immune cells that have accumulated in the endometrium are under the control of immune regulatory cells such as Treg and decidual cells 4,15,30–34 . Most likely, when the ovum begins to implant in the Fallopian tube and the immune cell infiltration into the tubal wall increases, the percentage of CD4 + CD25 + Foxp3 + positive lymphocytes in eutopic endometrium does not undergo sufficient alteration when compared with the degree of increase in Treg cell infiltration into the decidua that takes place during normal intrauterine pregnancy.…”
Section: Discussionmentioning
confidence: 99%